Associations between Variants of the 8q24 Chromosome and Nine Smoking-Related Cancer Sites - Park, Sungshim Lani; Chang, Shen-Chih; Cai, Lin; Cordon-Cardo, Carlos; Ding, Bao-Guo; Greenland, Sander; Hussain, Shehnaz K.; Jiang, Qingwu; Liu, Simin; Lu, Ming-Lan; Mao, Jenny T.; Morgenstern, Hal; et al. (Cancer epidemiology, biomarkers & prevention, 2008)
Recent genome-wide association studies identified key single nucleotide polymorphisms (SNPs) in the 8q24 region to be associated with prostate cancer. 8q24 SNPs have also been associated with colorectal cancer, suggesting that this region may not be specifically associated to just prostate cancer. To date, the association between these polymorphisms and tobacco smoking-related cancer sites remains unknown. Using epidemiologic data and biological samples previously collected in three case-control studies from U.S. and Chinese populations, we selected and genotyped one SNP from each of the three previously determined “regions” within the 8q24 loci, rs1447295 (region 1), rs16901979 (region 2), and rs6983267 (region 3), and examined their association with cancers of the lung, oropharynx, nasopharynx, larynx, esophagus, stomach, liver, bladder, and kidney. We observed noteworthy associations between rs6983267 and upper aerodigestive tract cancers [adjusted odds ratio (OR adj ), 1.69; 95% confidence interval (95% CI), 1.28-2.24], particularly in oropharynx (OR adj , 1.80; 95% CI, 1.30-2.49) and larynx (OR adj , 2.04; 95% CI, 1.12-3.72). We also observed a suggestive association between rs6983267 and liver cancer (OR adj , 1.51; 95% CI, 0.99-2.31). When we stratified our analysis by smoking status, rs6983267 was positively associated with lung cancer among ever-smokers (OR adj , 1.45; 95% CI, 1.05-2.00) and inversely associated with bladder cancer among ever-smokers (OR adj , 0.35; 95% CI, 0.14-0.83). Associations were observed between rs16901979 and upper aerodigestive tract cancer among never-smokers and between rs1447295 and liver cancer among ever-smokers. Our results suggest variants of the 8q24 chromosome may play an important role in smoking-related cancer development. Functional and large epidemiologic studies should be conducted to further investigate the association of 8q24 SNPs with smoking-related cancers. (Cancer Epidemiol Biomarkers Prev 2008;17(11):3193–202)